An update on rhabdomyosarcoma risk stratification and the rationale for current and future Children's Oncology Group clinical trials. Issue 4 (7th February 2022) - Haduong, Josephine H.; Heske, Christine M.; Allen‐Rhoades, Wendy; Xue, Wei; Teot, Lisa A.; Rodeberg, David A.; Donaldson, Sarah S.; Weiss, Aaron; Hawkins, Douglas S.; Venkatramani, Rajkumar
Abstract: Children and adolescents with rhabdomyosarcoma (RMS) comprise a heterogeneous population with variable overall survival rates ranging between approximately 6% and 100% depending on defined risk factors. Although the risk stratification of patients has been refined across five decades of collaborative group studies, molecular prognostic biomarkers beyond FOXO1 fusion status have yet to be incorporated prospectively in upfront risk‐based therapy assignments. This review describes the evolution of risk‐based therapy and the current risk stratification, defines a new risk stratification incorporating novel biomarkers, and provides the rationale for the current and upcoming Children's Oncology Group RMS studies.